ВДОСКОНАЛЕННЯ БІБЛІОТЕЧНО-БІБЛІОГРАФІЧНОГО ОБСЛУГОВУВАННЯ В БІБЛІОТЕЦІ ВНЗ (Педагогіка вищої та середньої школи, 2008)
Modern forms and methods of library-bibliographic service in the university library are being considered, the impontance of computerizing of libraries is stressed.